Giant hemorrhagic trochanteric bursitis mimicking a high-grade soft tissue sarcoma: report of two cases.: Giant trochanteric bursitis mimicking a high-grade soft tissue sarcoma - Toscano, Angelo; Costa, Giuseppe Gianluca; Rocchi, Martina; Saracco, Alvise; Pignatti, Giovanni (Acta Biomedica Atenei Parmensis, 2021)
Background: The giant haemorrhagic bursitis of the hip joint is a rare clinical condition that requires evidence-based guidelines for adequate diagnosis and management. Usually, this pathology requires conservative treatment; however, when abnormal size or clinical symptoms of compression of the surrounding noble structures are reported, an accurate differential diagnosis is required, in order to exclude other malignant conditions that can be included into differential diagnosis, and a surgical approach should be considered. The purpose of this work is to provide an appropriate description of the diagnostic and therapeutic path, providing an accurate analysis of the possible differential diagnoses. Methods: We report 2 cases of symptomatic haemorrhagic bursitis of the hip joint, confirmed by histological investigation. In both cases, the patients complained a peripheral nerve deficit of a single limb: one patient presented paresthesia of lateral femoral cutaneous nerve while the second peripheral edema due to compression of the proximal venous and lymphatic circulation. Results: Both cases were successfully managed by complete surgical excision of the mass, with no recurrence. There were no major complications, but in first case the nerve deficit was permanent. Conclusions: Giant hemorrhagic trochanteric bursitis is a rare condition, but it should be included in the differential diagnosis of soft tissue masses arising from the hip joint. Due to the rarity of this entity, a cautious exclusion process of all plausible differential diagnosis must be undertaken, in order to not miss the possibility of soft-tissue tumors, primarily malignant high-grade sarcomas.